Variations in the length of basilar artery In relation to different age groups - Sultana, Anjuman Ara; Ara, Shamim; Rahman, Mushfika; Akhter, Farhana; Shahin, Rebeka; Zaman, Farhana (Bangladesh Journal of Anatomy, 2017)
Context: Basilar artery is one of the main arteries that supplies the posterior portion of brain- occipital lobe, temporal lobe, cerebellum, mesencephalon, thalamas, pons and medulla. So the area supplied by basilar artery is also called posterior cerebral circulation. Basilar artery is the most important artery in the posterior circulation. Basilar artery, supplies the anatomical structures within the posterior cranial fossa of brain. The Circle of Willis is the principal arterial anastomotic trunk of brain formed by anastomosis between the branches of internal carotid arteries and terminal branch of basilar artery. It is responsible for collateral circulation of brain, specially of old people, who have reduced blood supply to brain due to senile arteriosclerosis. Cerebrovascular diseases due to basilar artery is more common in men than women. Thrombosis in basilar artery causes devastating effect like coma, flaccid quadriplegia, areflexia, complete anesthesia, pin point pupil and hyperpyrexia. Basilar artery related clinical conditions are, posterior circulation stroke, migraine, tumor, aneurysm, and arteriovenous malformation (AVM), revascularization procedure etc. Anatomy of basilar artery and its branches are very complex and variable. So, detailed morphological knowledge is essential for proper diagnosis and treatment of neurological disorders. Objective: To identify variations in the length of basilar artery in relation to advancing age. Study Design: A cross-sectional descriptive type of study. Place & period of Study: The study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka, from January 2010 to December 2010. Materials: 70 postmortem basilar arteries were collected from unclaimed dead bodies that were under examination in the morgue of Department of Forensic medicine, Dhaka Medical College Dhaka. The study was approved by the Ethical Review Committee (ERC) of Dhaka Medical College. Methods: The samples were divided into three different age groups i.e. Group A (15 -30 years), Group- B (31-45 years) and Group-C (46-60 years). After fixation of the whole of the human brain with formalin, the basilar artery and its branches were collected along with the brainstem by giving a incision on middle cerebellar peduncle & thus separated from cerebellum. The moisture over the arteries were removed by using filter paper. Length of the basilar artery was measured by using a digital slide caliper. Results: The mean ± SD length of the basilar artery was found 23.92 ± 1.35 mm in group A, 24.44 ± 1.33 mm in group B & 25.69 ± 2.24 mm in group C. The highest value was found in group C and the lowest one was found in group A. The differences between group A and group C and group B and group C were statistically significant (p<0.05). Conclusion: Present study showed that there was gradual increase in length of basilar artery with advancing age which was statistically significant in different age groups (p<0.05). Further studies to find out the cause and functional / clinical correlations of this variation are recommended. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 2 , pp. 63-66